2023
DOI: 10.1002/oby.23848
|View full text |Cite
|
Sign up to set email alerts
|

Are 24‐hour movement recommendations associated with obesity‐related indicators in the young population? A meta‐analysis

José Francisco López‐Gil,
Miguel Angel Tapia‐Serrano,
Javier Sevil‐Serrano
et al.

Abstract: ObjectiveThis study aimed to determine the relationship between meeting all three 24‐hour movement recommendations (i.e., physical activity, sleep duration, and screen time) and obesity‐related indicators among young people.MethodsFour databases were systematically searched (PubMed, Scopus, Web of Science, and Cochrane Library).ResultsMeeting the 24‐hour movement recommendations was cross‐sectionally associated with lower overall obesity‐related indicators (r = −0.09, 95% CI: −0.11 to −0.06), but no longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 104 publications
(194 reference statements)
0
4
0
Order By: Relevance
“…In addition, García-Hermoso et al (64) observed that physical education attendance [which is closely related to physical literacy (67)] was linked with meeting all three 24-h movement recommendations (i.e., physical activity, screen time, and sleep duration) in adolescents, and this association was maintained in adulthood. Supporting this idea, a meta-analysis by López-Gil et al (7) has revealed that meeting all these 24-h movement recommendations has been related to lower obesity-related outcomes (i.e., excess weight, obesity, BMI, BMI z score, waist circumference, and body fat). Given the propensity of healthy behaviors to cluster together (e.g., diet, physical activity) (68-71), it is possible that a greater PPL led to a healthier lifestyle, which could favor an optimal body weight and body composition in adolescents.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, García-Hermoso et al (64) observed that physical education attendance [which is closely related to physical literacy (67)] was linked with meeting all three 24-h movement recommendations (i.e., physical activity, screen time, and sleep duration) in adolescents, and this association was maintained in adulthood. Supporting this idea, a meta-analysis by López-Gil et al (7) has revealed that meeting all these 24-h movement recommendations has been related to lower obesity-related outcomes (i.e., excess weight, obesity, BMI, BMI z score, waist circumference, and body fat). Given the propensity of healthy behaviors to cluster together (e.g., diet, physical activity) (68-71), it is possible that a greater PPL led to a healthier lifestyle, which could favor an optimal body weight and body composition in adolescents.…”
Section: Discussionmentioning
confidence: 97%
“…Numerous studies indicate that promoting and sustaining healthy lifestyle behaviors can serve as an effective approach to prevent obesity among the young population ( 7 10 ). In recent times, there has been a significant surge in the attention given to physical literacy, leading to the emergence of various programs, curricula, and policies aimed at enhancing it ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The lower level of participants engaging in low physical activity could be a possible explanation for this result. Although the analyses were adjusted for physical activity, those who exercised less may also be more likely to engage in other behaviors that are risk factors for obesity but were not measured in the COMBAT survey (i.e., optimal sleep duration, sedentary behaviors) [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given this aspect, the World Health Organization recommends carrying out at least 60 min a day of physical activity of moderate to vigorous intensity for children and adolescents [6]. Accordingly, it is shown that a higher level of physical activity is relationship with a lower likelihood of being overweight or obese [7,8]. Moreover, greater physical, psychosocial, and cognitive benefits are associated with regular physical activity [9].…”
Section: Introductionmentioning
confidence: 99%